Pengaruh Kemasan dan Label Halal terhadap Keputusan Pembelian Produk Kosmetik Hanasui (Studi Kasus pada Mahasiswi Universitas Prabumulih) - Zayudi; M.Robby Kaharuddin; Hairunnisa (Equivalent : Journal of Economic, Accounting and Management, 2026)
Abstract : This study aims to examine the effect of packaging and halal labeling on purchasing decisions of Hanasui cosmetic products among female students at Prabumulih University. The research employed a quantitative approach using survey methods by distributing questionnaires to 102 respondents who had previously used Hanasui cosmetics. Data were analyzed using multiple linear regression with the assistance of SPSS version 30. The results indicate that packaging has a positive and significant effect on purchasing decisions, as evidenced by a t-value greater than the critical value and a significance level below 0.05. Halal labeling also shows a positive and significant influence on purchasing decisions. Simultaneously, packaging and halal labeling significantly affect purchasing decisions, with an F-value of 40.578 and a significance level of 0.001. The coefficient of determination (R²) is 0.450, indicating that packaging and halal labeling explain 45% of the variation in purchasing decisions, while the remaining 55% is influenced by other factors not examined in this study. These findings suggest that both packaging quality and halal labeling play important roles in shaping consumer purchasing decisions for Hanasui cosmetic products. Abstrak : Penelitian ini bertujuan untuk mengetahui pengaruh kemasan dan label halal terhadap keputusan pembelian kosmetik Hanasui pada mahasiswi Universitas Prabumulih. Metode penelitian menggunakan pendekatan kuantitatif dengan penyebaran kuesioner kepada 102 responden, dan analisis data dilakukan menggunakan SPSS versi 30. Hasil penelitian menunjukkan bahwa secara parsial kemasan dan label halal berpengaruh signifikan terhadap keputusan pembelian, dengan nilai t hitung masing masing lebih besar dari t tabel serta signifikansi < 0,05. Secara simultan, kedua variabel juga berpengaruh signifikan dengan nilai F hitung 40,578 > F tabel 3,089 dan sig 0,001. Nilai koefisien determinasi (R²) sebesar 0,450, artinya kemasan dan label halal menjelaskan 45% keputusan pembelian, sedangkan sisanya 55% dipengaruhi faktor lain. Penelitian ini menyimpulkan bahwa kemasan dan label halal merupakan faktor penting yang memengaruhi keputusan pembelian kosmetik Hanasui pada mahasiswi Universitas Prabumulih. Kata Kunci: Kemasan, Label Halal, Keputusan Pembelian, Kosmetik Hanasui.